2022
DOI: 10.1108/lodj-04-2021-0162
|View full text |Cite
|
Sign up to set email alerts
|

Fostering exploration and exploitation behavior in management teams to enhance organizational performance: the LearnOvation leadership development program

Abstract: PurposeThe purpose of this paper is to assess the impact and effectiveness of the LearnOvation leadership development program in the welfare services sector in Sweden.Design/methodology/approachLearnOvation was based on ambidexterity theory for the program content and the research study design. A mixed-method design was applied, using questionnaires among staff (n = 523) and written evaluations with the management teams (n = 60).FindingsQuantitative analysis of the questionnaires indicated little change in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 48 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…In addition, Zhang et al (2022b) showed that empowering leadership and psychological empowerment were related to high innovation capacity. Employees tend to engage in creative and innovative activities when their leaders offer them empowering leadership feedback (Kim et al, 2018;Kjellstr€ om et al, 2022). As such, this empowering feedback encourages exploratory activities.…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Zhang et al (2022b) showed that empowering leadership and psychological empowerment were related to high innovation capacity. Employees tend to engage in creative and innovative activities when their leaders offer them empowering leadership feedback (Kim et al, 2018;Kjellstr€ om et al, 2022). As such, this empowering feedback encourages exploratory activities.…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
“…Past empirical research has shown that empowering leadership can promote various elements of organizational exploration, such as experimentation and innovation (Dahleez et al, 2022;Kim and Beehr, 2022;Kim et al, 2018;Kjellstr€ om et al, 2022;Lin et al, 2022;Naqshbandi et al, 2019;Rohlfer et al, 2022;Supriyanto et al, 2023;Zhang et al, 2022a, b). Aiming to advance theoretical and empirical research on the relationship between empowering leadership and organizational exploration per se (and not only several of its components), we tested the indirect relationship between empowering leadership and organizational exploration through preoccupation with failure.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature concerning organizational ambidexterity (OA), which encompasses exploration and exploitation, has been widely explored. Furthermore, the OA framework has been tested and supported across various contexts (Hardy III et al, 2019; Kjellström et al, 2022; Zacher et al, 2016). As such, the exploration-exploitation has been empirically demonstrated in the management literature, which provides a solid foundation to establish and propose our 3-E typology in the workplace context.…”
Section: Workplace Learning and Social Networkmentioning
confidence: 99%
“…Exploration and exploitation represent knowledge expansion and refinement, respectively (Hardy III et al, 2019). Although the typology was coined to describe organizational-level learning strategies (March, 1991), it can be applied to individual-level learning to explain individuals’ distinct strategic choices, mindsets (Greco et al, 2019), and behaviors (Hardy III et al, 2019; Kjellström et al, 2022; Zacher et al, 2016).…”
Section: Workplace Learning and Social Networkmentioning
confidence: 99%